Multi-Track Diplomacy by Ibrahimy University Students in Introducing the Islamic Boarding School Based-Education System in Narathiwat, Thailand - Inayah, Nailul; Nurika, Rizki Rahmadini (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
This study examines the multi-track diplomacy carried out by students of Ibrahimy University in introducing the Islamic boarding school (pesantren)-based education system in Islamic schools in Narathiwat Province, Thailand. The presence of these students has become a strategic means of introducing the Islamic boarding school education model, which integrates religious and general curricula and emphasizes a boarding school system, values of independence, togetherness, and spiritual guidance. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews and documentation, and is analyzed through source triangulation. The results show that the students represent the practice of multi-track diplomacy in Track 5 (education, training, and research) through the International Field Experience Program (PPL). They contribute as non-state actors who strengthen cross-cultural relations and encourage the transformation of the education system in partner schools. This is reflected in the construction of boarding facilities at Amaniah School as the first step in implementing the Islamic boarding school education system.